Dynamics of the electron beam generated by the magnetron gun with different configurations of the magnetic field in the transportation channel - Mazmanishvili, O.S.; Reshetnyak, M.G.; Romasko, V.P.; Chertishchev, I.A. (Вопросы атомной науки и техники, 2021)
The dynamics of the dimensions of the electron beam generated by the magnetron gun in the particle transport channel and the efficiency of focusing the tubular electron beam in the gradient magnetic field are investigated. The experiments were carried out with magnetron guns with secondary-emission cathodes (cathode diameters 36 and 16 mm, anodes diameters 78 and 36 mm) at cathode voltage of 20…80 kV. Magnetic fields were created both by the solenoid and jointly by the solenoid and the permanent magnet. The dependence of the radial distribution of the beam on metal targets on the amplitude and gradient of the magnetic field along the axis of the system is investigated. The possibility of controlling the beam diameter by varying the magnetic field is shown. The imprints of collimated beams were obtained experimentally on targets located at selected distances. The obtained experimental data agree with the results of numerical simulation. It is shown that with an increase in the amplitude of the gradient magnetic field, the effect of radial focusing of the beam is more pronounced. Досліджено динаміку електронного пучка, що генерується магнетронною гарматою, в каналі транспортування частинок і ефективність фокусування трубчастого електронного потоку в градієнтному магнітному полі. Експерименти проводилися з магнетронними гарматами зі вторинно-емісійними катодами (діаметри катодів 36 і 16 мм, анодів 78 і 36 мм) при напрузі на катоді 20…80 кВ. Магнітні поля створювалися як соленоїдом, так і спільно соленоїдом і постійним магнітом. Досліджено залежність радіального розподілу пучка на металевих мішенях від амплітуди і градієнта магнітного поля уздовж осі системи. Показана можливість регулювання діаметра пучка шляхом варіації розподілу магнітного поля. Отримано відбитки колімованих пучків на мішенях, розташованих на обраних відстанях. Встановлено, що зі збільшенням амплітуди магнітного поля ефект радіального фокусування пучка є більше виражений. Исследована динамика размеров электронного пучка, генерируемого магнетронной пушкой, в канале транспортировки частиц и эффективность фокусировки трубчатого электронного потока в градиентном магнитном поле. Эксперименты проводились с магнетронными пушками с вторично-эмиссионными катодами (диаметр катодов 36 и 16 мм, диаметр анодов 78 и 36 мм) при напряжении на катоде 20…80 кВ. Магнитные поля создавались как соленоидом, так и совместно соленоидом и постоянным магнитом. Исследована зависимость радиального распределения пучка на металлических мишенях от амплитуды и градиента магнитного поля вдоль оси системы. Показана возможность регулирования диаметра пучка путем вариации магнитного поля. Экспериментально получены отпечатки коллимированных пучков на мишенях, расположенных на выбранных расстояниях. Полученные экспериментальные данные согласуются с результатами численного моделирования. Показано, что с увеличением амплитуды градиентного магнитного поля эффект радиального фокусирования пучка больше выражен.